Semiotics’ Internal Conflict. The role of pragmatic processing in the constitution of meaning - Penco, Carlo; Domaneschi, Filippo (Rivista Italiana di Filosofia del Linguaggio, 1970)
The aim of this paper is to give a short overview of the debate on the boundaries between semantics and pragmatics, and to point out both its origins and the main problem behind: the definition of what is said. Many participants in the debate challenge the standard view proposed by Paul Grice between literal (semantic) meaning given by conventions and speaker’s meaning given by intentions. In 1. we will trace the origin of the problem in some early definitions of semiotics and in the development of Kaplan’s theory of demonstratives; in 2. we will then give a general assessment of what is at stake: the notion of what is said, or propositional content; in 3. we present some of the main alternatives on the market; in 4. we will claim that the rigid distinction between metaphysical and epistemological aspects of meaning is not so rigid after all, and there is space for pragmatic processing in the constitution of meaning – of what is said.